Work, risk and health: Differences between immigrants and natives in Spain - Meritxell Solé; Luis Diaz-Serrano; Marisol Rodriguez Martinez (Institute for the Study of Labor (IZA), 2010)
We analyze the impact of working and contractual conditions, particularly exposure to job risks, on the probability of acquiring a disability. We postulate a model in which this impact is mediated by the choice of occupation, with a level of risk associated to it. We assume this choice is endogenous, and that it depends on preferences and opportunities in the labour market, both of which may differ between immigrants and natives. To test this hypothesis we use data from the Continuous Sample of Working Lives of the Spanish SS system. It contains individual, job and firm information of over a million workers, including a representative sample of immigrants. We find that risk exposure increases the probability of permanent disability by 5.3%; temporary employment also influences health. Migrant status - with differences among regions of origin - significantly affects both disability and the probability of being employed in a risky occupation. Most groups of immigrants work in riskier jobs, but have lower probability of becoming disabled. Nevertheless, our theoretical hypothesis that disability and risk are jointly determined is not valid for immigrants: i.e. for them working conditions is not a matter of choice in terms of health.
Keywords: J28; J61; J81; 330; disability; working conditions; immigration; Spain; MCVL